Shape optimization in computational fluid dynamics - Dinh, Quang Vinh; Roge, Gilbert; Sevin, Cyrille; Stoumet, Bruno (European Journal of Computational Mechanics, 1996)
This paper is devoted to shape optimization for Partial Differential Equations ( PDE) systems related to Computational Fluid Dynamics (CFD ). Numerical approximation of the PDE's relies on schemes satisfying discrete maximum principles and using unstructured meshes generated from the shape parameters. The theory of control is applied to the discrete design problem with the resulting constrained optimization problem solved by gradient based algorithms. An automatic differentiation procedure for Fortran codes is extensively used to carry out the CFD sensitivity analysis.